1987
DOI: 10.1002/bjs.1800740417
|View full text |Cite
|
Sign up to set email alerts
|

Acute superior mesenteric ischaemia

Abstract: A review of case records and post-mortem reports from Glasgow Royal Infirmary over the past 12 years identified 102 patients with acute superior mesenteric ischaemia, 53 (52 per cent) of whom were first diagnosed at post mortem. Overall mortality was 92 per cent and mortality in the 49 patients diagnosed in life was 84 per cent. Fourteen patients (14 per cent) underwent exploratory laparotomy only with no survivors, 26 (25 per cent) had bowel resection alone with 7 surviving, and 9 (9 per cent) had a revascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 8 publications
4
49
0
4
Order By: Relevance
“…Even limited resection resulted in complications in 42% of patients and death in 12%. In any series the overall morbidity and mortality rates reflect the number of massive resections performed which are associated with a greater risk of complications and deaths both in the present study and other reports [2,3], Massive resection was more than twice as likely to result in postoperative complications and over three times as likely to result in a postoperative death than a limited resection. Massive resections were nearly always done on emergency and frequently (48%) resulted in loss of intestinal continuity, most likely because they were performed on ischemic, unprepared intestine in an emergency setting.…”
Section: Discussionsupporting
confidence: 71%
“…Even limited resection resulted in complications in 42% of patients and death in 12%. In any series the overall morbidity and mortality rates reflect the number of massive resections performed which are associated with a greater risk of complications and deaths both in the present study and other reports [2,3], Massive resection was more than twice as likely to result in postoperative complications and over three times as likely to result in a postoperative death than a limited resection. Massive resections were nearly always done on emergency and frequently (48%) resulted in loss of intestinal continuity, most likely because they were performed on ischemic, unprepared intestine in an emergency setting.…”
Section: Discussionsupporting
confidence: 71%
“…AMI represents 10%-67% of these complications [129,133,134] , and is the most lethal, with a case-fatality rate of 70% to 100% [129,131,132,135,136] . Pathophysiology AMI occurring after CPB, is due to NOMI in the vast majority of cases [137][138][139] . The various contributory factors are: low cardiac output (frequent in this category of patients), use of vasopressors and underlying atherosclerotic disease.…”
Section: Ami After Cpbmentioning
confidence: 99%
“…2,14,15 In present study patients appeared later had increase mortality rates (50%-100%) similarly to the studies done by others in which they reported increased mortality (up to 90% to 100%) in bowel ischemia patients due to undue delay in presentation, the shorter the duration of symptoms the more likely was the chance of patient to survive after surgery. 16,17 Forty eight percent of patients of bowel ischemia group had no significant X ray abdomen findings. These finding were similar to the findings of the study done by others in which they had reported approximately 50% patients had no significant X ray abdomen findings.…”
Section: Discussionmentioning
confidence: 97%